AI Robot – Companion, Friend or Competitor of Human Being? - Wieczorek, Krzysztof T. (Philosophy and Canon Law, 2023)
Robots are becoming part of people’s everyday surroundings. Therefore, the formation and change of people’s attitude towards objects equipped with artificial intelligence is becoming an important subject of reflection. Substantial research has already been conducted, but few predictions have been made about the future relationship between humanity and autonomous, multi-tasking and highly advanced artificial intelligence. The purpose of this article is an attempt at extrapolating the evolution of the human-robot bond so far, from alienation and a sense of threat toward tameness, affection and even―perhaps―friendship. The study of the evolution of the relationship between humans and artificial intelligence makes it also possible to deepen our understanding of who human beings are, what their needs, expectations, and hopes are, and which of them can be realized through close cooperation between humans and artificial intelligence.